2024
DOI: 10.1038/s41467-024-47367-5
|View full text |Cite
|
Sign up to set email alerts
|

Artificial kagome lattices of Shockley surface states patterned by halogen hydrogen-bonded organic frameworks

Ruoting Yin,
Xiang Zhu,
Qiang Fu
et al.

Abstract: Artificial electronic kagome lattices may emerge from electronic potential landscapes using customized structures with exotic supersymmetries, benefiting from the confinement of Shockley surface-state electrons on coinage metals, which offers a flexible approach to realizing intriguing quantum phases of matter that are highly desired but scarce in available kagome materials. Here, we devise a general strategy to construct varieties of electronic kagome lattices by utilizing the on-surface synthesis of halogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…Electronically, the present lattice can be viewed as a hybrid of honeycomb and kagome lattices. While this lattice model has been called star lattice or diatomic kagome lattice, , we refer to it as honeycomb-kagome lattice to stress its hybrid character. In the two limiting cases of t 0 / t 1 → ∞ and t 0 / t 1 → 0, it corresponds to the pure honeycomb and kagome lattices, respectively (Figure b).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Electronically, the present lattice can be viewed as a hybrid of honeycomb and kagome lattices. While this lattice model has been called star lattice or diatomic kagome lattice, , we refer to it as honeycomb-kagome lattice to stress its hybrid character. In the two limiting cases of t 0 / t 1 → ∞ and t 0 / t 1 → 0, it corresponds to the pure honeycomb and kagome lattices, respectively (Figure b).…”
Section: Resultsmentioning
confidence: 99%
“…These Dirac and flat bands are under intensive investigations because of rich topological and/or many-body phenomena, but most of them are based on naturally grown inorganic materials and thus lack controllability of model parameters. One of the promising methods for extending the research realm is the usage of molecular assembly such as supramolecules and metal–organic/covalent-organic frameworks, where 2D electronic lattices are defined by intermolecular networks , or localized Schockley surface states coupled through molecular potential barriers. ,, This approach is based on the rational design of molecules and thus can be very flexible and powerful. However, intermolecular coupling is often very weak, and the general strategy for the formation of a molecular-based honeycomb lattice has not been established yet.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The local density of states (LDOS) showed that the 2D organometallic coordination network is semiconducting with a bandgap of 2.3 eV. The corresponding band structure showed no obvious flat band near the Fermi energy, which can be attributed to the asymmetry of the Kagome structure caused by the heterogeneous coordination PGI nodes. , …”
mentioning
confidence: 99%
“…The corresponding band structure showed no obvious flat band near the Fermi energy, which can be attributed to the asymmetry of the Kagome structure caused by the heterogeneous coordination PGI nodes. 63,64 Furthermore, we analyzed the charge density difference between the organic ligands and Au adatoms on Au(111). Compared with the 1D metal−organic coordination chain with IGI nodes, a significant amount of charge was redistributed in the 2D organometallic coordination network with PGI nodes (Figure 3e).…”
mentioning
confidence: 99%